Effect of Hardening to drought tolerance on the moisture contents of sunflower plant. II moisture percentage in leaves and heads (Baghdad Science Journal, 2025)
The objective of this work was to study the changes in the moisture content of the leaves and heads of sunflower plant during growth stages under hardening conditions to drought tolerance . Field experiment was carried out during the spring season of 2000 and 2001. Asplit-split plots design was used with three replications. The main plots included irrigation treatments:irrigation to 100%(full irrigation), 75and50%of available water.The sub plots were the cultivars Euroflor and Flame.The sub-sub plots represented four seed soaking treatments :Control (unsoaked), soaking in water ,Paclobutrazol solution(250ppm),and Pix solution (500ppm). The soaking continued for 24 hours then seeds were dried at room temperature until they regained their original weight. Amount of water for each irrigation were calculated to satisfy water depletion in soil using a neutron meter.Results indicated that moisture content of the leaves was not affected by irrigation treatments .While full irrigation and stress 600 Kp increased moisture content of heads by 1.69 and 2.44%, respectively than stress 800Kp after 58 days from planting in the season 2001.Full irrigation was superior over stress 600 and 800 Kp by 3.66and 1.52% after 72 days from planting as a mean of seasons. Euroflor was superior over Flame in the moisture content of its leaves after86 days from planting by 5.34% in the season of 2001 and by 2.76% as a mean of seasons , and superior in moisture content of its heads by 2.79% in the season of 2001. Soaking in water , paclobutrazol and pix solutions increased moisture content of sunflower leaves by 3.73,2.65 and 4.13% after 58 days from planting as a mean of seasons, and increased moisture content of sunflower heads by 4.05, 5.12 and 5.44% after 58 days from planting in the season 2000 , and by 2.80, 3.09 and 2.86% in the seasons of 2001 compared with unsoaked treatment. In conclusion , soaking the seeds presowing in water or plant growth regulators could improve water relations of the leaves and heads of sunflower plants , which lead to increase flowering, setting and filling of seeds during drought periods.